Trauma Ties in Paul Auster’s Invention of Solitude - Houaria Righi (Sillages Critiques)
The Invention of Solitude functions as the cornerstone of Paul Auster’s work. It discusses the writer’s fundamental themes. It can be considered as an autobiography as it was inspired by a striking familial trauma, but also as an essay, since in this hybrid piece of work Auster puts into question the very nature of the relationship and drags the reader along the maze of creation. Our aim is to focus on the way trauma redefines the very nature of a relationship.